Non-aqueous electrolyte and lithium ion battery containing same
By introducing benzenesulfonyl fluoride and carbonate sulfate compounds into the non-aqueous electrolyte of lithium-ion batteries, a stable SEI film is formed, which solves the problem of interface instability of lithium-ion batteries under high voltage and improves the high-temperature circulation and storage performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202510672410.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-23
- Publication Date
- 2025-08-05
AI Technical Summary
Existing lithium-ion batteries have unstable electrolyte-electrode interfaces at high voltages, resulting in dendrite lithium growth, electrolyte decomposition and electrochemically active transition metal dissolution, affecting cycling and storage performance.
Beneficiaryl sulfonyl fluoride compounds and carbonate sulfate compounds are introduced as additives in the non-aqueous electrolyte solution to form a stable solid electrolyte interface film (SEI), which improves the lithium ion transmission rate and improves the high-temperature cycling performance.
Through synergistic action, the lithium-ion transmission rate of lithium-ion batteries can be improved, internal resistance can be reduced, and high-temperature storage and cycling performance can be improved.
Smart Images

Figure CN120432646A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a non-aqueous electrolyte and a lithium ion battery containing the non-aqueous electrolyte. Background Art
[0002] Over the past two decades, lithium-ion batteries have dominated the energy storage market due to their high energy density. With the rapidly growing demand for even higher energy density, high-voltage nickel-rich layered cathodes have emerged as a promising strategy for next-generation high-energy batteries. However, achieving high-voltage lithium-ion batteries relies heavily on the stability of the electrolyte-electrode interface.
[0003] The unstable SEI layer formed by traditional carbonate-based electrolytes lacks sufficient mechanical robustness during lithium plating / stripping processes and cannot withstand the large volume changes during cycling, resulting in undesirable lithium dendrite growth and electrolyte consumption. In addition, the high cutoff voltage induces electrolyte decomposition and the formation of a cathode electrode interphase (CEI) layer. The unstable CEI can be damaged by trace hydrofluoric acid impurities produced by the decomposition of lithium hexafluorophosphate in the electrolyte, inducing persistent side reactions, destabilizing the CEI structure, and accelerating capacity decay by extracting electrochemically active transition metals from the cathode. Therefore, higher requirements are placed on the cycling performance, storage performance, and cycle impedance of high-voltage batteries. Therefore, it is urgent to develop an electrolyte suitable for power-type high-voltage batteries to address the shortcomings of existing technologies. Summary of the Invention
[0004] In view of the above problems, the object of the present invention is to provide a non-aqueous electrolyte and a lithium-ion battery containing the non-aqueous electrolyte. Introducing benzenesulfonyl fluoride compounds and polyol carbonate bisulfate compounds as additives into the non-aqueous electrolyte can improve the high-temperature cycle performance of the lithium-ion battery, while reducing the internal resistance and improving the high-temperature storage performance of the lithium-ion battery.
[0005] To achieve the above-mentioned object, the present invention provides a non-aqueous electrolyte comprising a lithium salt, a non-aqueous organic solvent and an additive, wherein the additive comprises a benzenesulfonyl fluoride compound shown in structural formula 1 and a carbonate bisulfate compound shown in structural formula 2.
[0006] wherein R1 to R5 are independently selected from hydrogen atoms, halogen atoms, amino groups, substituted or unsubstituted C1 to C 10 Alkyl, substituted or unsubstituted C2 to C 10 Alkenyl, substituted or unsubstituted C2 to C 10 Alkynyl, R6 to R7 are each independently selected from hydrogen atom, or , * indicates the connection end.
[0007] Compared with the prior art, the additives of the non-aqueous electrolyte of the present invention include benzenesulfonyl fluoride compounds and carbonate bisulfate compounds. Among them, the benzenesulfonyl fluoride compound can form an inorganic component rich in Li2S and LiF with high ionic conductivity when forming a film on the negative electrode side, which can effectively accelerate the lithium ion transmission rate and improve the rate fast charging performance of lithium ion batteries. Although the SF bond in the benzenesulfonyl fluoride (ArSO2F) molecule has a certain stability at room temperature, under high temperature conditions, thermal energy may cause the SF bond to break. This thermal cracking will cause the benzenesulfonyl fluoride to decompose into benzenesulfonyl (ArSO 2⁻ ) and fluoride ions (F⁻), resulting in reduced stability. In addition, the electron cloud distribution on the benzene ring will change under high temperature conditions, thereby affecting the stability of the sulfonyl fluoride group. The present invention further introduces carbonate bisulfate compounds into the non-aqueous electrolyte, which can synergistically regulate the components of the solid electrolyte membrane. The sulfate structure contained therein is reduced to form lithium sulfate Li2SO4 and alkyl lithium sulfate (ROSO3Li), while the carbonate structure is reduced to form alkyl lithium carbonate (ROCO2Li) and lithium carbonate (Li2CO3) and other components. These components help to form a stable solid electrolyte interface film (SEI). This stable SEI film may reduce the side reactions between the electrode and the electrolyte at high temperatures. At the same time, -OS(=O)2O in the sulfur-containing compounds and their decomposition products on the positive electrode side - Group, which can react with the transition metal (Ni 2+ , Mn 2+ / Mn 3+ ) complexation, improve the interface stability of the positive electrode electrolyte and inhibit the dissolution of transition metals to a certain extent. In addition, carbonate bisulfate compounds can regulate the solvation structure. The sulfoxide groups they contain have strong polarity, which can increase the overall polarity of the electrolyte and make Li + The solvation sheath is more stable. This highly polar environment may inhibit the local charge separation of the fluorine atoms in benzenesulfonyl fluoride, thereby reducing the reactivity and decomposition rate of benzenesulfonyl fluoride at high temperatures. Therefore, the present invention, through the synergistic effect between benzenesulfonyl fluoride compounds and carbonate bisulfate compounds, can effectively improve the lithium ion transport rate and fast-rate charging performance of lithium-ion batteries, and improve the high-temperature storage performance and high-temperature cycling performance of lithium-ion batteries.
[0008] As a preferred technical solution, R1-R5 are each independently selected from a hydrogen atom, an amino group, a substituted or unsubstituted C1 to C6 alkyl group, and at least one of R6-R7 is a hydrogen atom.
[0009] As a preferred technical solution, the benzenesulfonyl fluoride compound is selected from at least one of Compounds 1 to 5.
[0010] .
[0011] As a preferred technical solution, the carbonate bisulfate compound is selected from at least one of Compound 6 to Compound 9.
[0012] .
[0013] As a preferred technical solution, the mass percentage of the benzenesulfonyl fluoride compound in the non-aqueous electrolyte is 0.05% to 5%. Preferably, the mass percentage of the benzenesulfonyl fluoride compound in the non-aqueous electrolyte is 0.1% to 2%. More preferably, the mass percentage of the benzenesulfonyl fluoride compound in the non-aqueous electrolyte is 0.1% to 1%. As an example, the mass percentage of the benzenesulfonyl fluoride compound in the non-aqueous electrolyte can be, but is not limited to, 0.05%, 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5%.
[0014] As a preferred technical solution, the mass percentage of the carbonate bisulfate compound in the non-aqueous electrolyte is 0.05-5. Preferably, the mass percentage of the carbonate bisulfate compound in the non-aqueous electrolyte is 0.1%-4%. More preferably, the mass percentage of the carbonate bisulfate compound in the non-aqueous electrolyte is 0.5%-2%. As an example, the mass percentage of the carbonate bisulfate compound in the non-aqueous electrolyte can be, but is not limited to, 0.05%, 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5%.
[0015] As a preferred technical solution, the lithium salt is selected from at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI), lithium bis(oxalatoborate) (LiBOB), lithium difluorophosphate (LiPO2F2), lithium fluorosulfonate (LiSO2F), lithium lower aliphatic carboxylates, lithium difluorobis(oxalatophosphate), and lithium bis(fluorosulfonyl imide). By way of example, the lithium salt is lithium hexafluorophosphate (LiPF6), but is not limited thereto. Furthermore, the lithium salt is a mixture of lithium hexafluorophosphate (LiPF6) and lithium bis(oxalatoborate) (LiBOB), but is not limited thereto.
[0016] Specifically, the mass percentage of the lithium salt in the non-aqueous electrolyte is 5-25%. Further, the mass percentage of the lithium salt in the non-aqueous electrolyte is 8-20%. More preferably, the mass percentage of the lithium salt in the non-aqueous electrolyte is 10-15%. As an example, the mass percentage of the lithium salt in the non-aqueous electrolyte may be, but is not limited to, 5%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 20%, 22%, 24%, and 25%.
[0017] As a preferred technical solution, the non-aqueous organic solvent is selected from γ-butyrolactone (GBL), γ-valerolactone (GVL), δ-valerolactone (DVL), methyl acetate (MA), ethyl acetate (EA), ethyl propionate (EP), butyl acetate (BAC), propyl propionate (PP), butyl propionate (PRB), ethylene carbonate (EC), propylene carbonate (PCA), butylene carbonate (BC), vinylene carbonate (VEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl n-propyl carbonate ( At least one of ethyl acetate, propylene carbonate (PC), 1,3-dioxolane (DOL), 1,4-dioxolane (DX), crown ether, tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-CH3-THF), 2-trifluoromethyltetrahydrofuran (2-CF3-THF), dimethoxymethane (DMM), diethoxymethane (DEM), ethoxymethoxymethane (DCE), ethylene glycol di-n-propyl ether (EDP), ethylene glycol di-n-butyl ether (EDB), and diethylene glycol dimethyl ether (DEGME).
[0018] Specifically, the mass percentage of the non-aqueous organic solvent in the non-aqueous electrolyte is 65% to 90%. Preferably, the mass percentage of the non-aqueous organic solvent in the non-aqueous electrolyte is 75% to 89%. More preferably, the mass percentage of the non-aqueous organic solvent in the non-aqueous electrolyte is 78% to 88%. By way of example, the mass percentage of the non-aqueous organic solvent in the non-aqueous electrolyte can be, but is not limited to, 65%, 70%, 80%, 85%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, or 90%.
[0019] As a preferred technical solution, the non-aqueous electrolyte of the present invention further includes an auxiliary agent, which is selected from at least one of fluoroethylene carbonate (FEC), vinylene carbonate (VC), 1,3-propane sultone (PS), diethylene sulfate (DTD), 1,3-propylene glycol cyclic sulfate (PCS), 1,4-butane sultone (1,4-BS), triallyl phosphate (TAP) and succinic anhydride (SA).
[0020] Another aspect of the present invention provides a lithium-ion battery comprising a positive electrode material, a negative electrode material and the aforementioned non-aqueous electrolyte, wherein the positive electrode material is selected from nickel-cobalt-manganese oxide.
[0021] As a better technical solution, the nickel-cobalt-manganese oxide material is high nickel-cobalt-manganese oxide LiNi x Co y Mn (1-x-y) M z O2, wherein 0.6≤x<0.9, x+y≤1, 0≤z<0.08, and M is at least one of Al, Mg, Zr, and Ti. As an example, the positive electrode material of the present invention is LiNi 0.6 Co 0.2 Mn 0.2 As a preferred technical solution, the negative electrode material is selected from at least one of artificial graphite, natural graphite, lithium titanate, silicon-carbon composite material, and silicon oxide. As an example, the negative electrode material is artificial graphite, but is not limited thereto. DETAILED DESCRIPTION
[0022] (1) Preparation of non-aqueous electrolyte Under an argon atmosphere and in a vacuum glove box with a moisture content of <1ppm, ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a weight ratio of EC:EMC=3:7 to prepare 86.3g of a non-aqueous organic solvent. 0.2g of compound 1 and 0.5g of compound 6 were added, dissolved, and stirred thoroughly. After that, 12.5g of lithium hexafluorophosphate (LiPF6) was added and mixed evenly to obtain a non-aqueous electrolyte.
[0023] (2) Preparation of positive electrode LiNi cobalt manganese oxide material 0.6 Co 0.2 Mn 0.2 , adhesive PVDF and conductive agent SuperP are evenly mixed in a mass ratio of 96:2.5:1.5 to form a lithium secondary battery positive electrode slurry with a certain viscosity. The mixed slurry is coated on both sides of an aluminum foil, dried, and rolled to obtain a positive electrode sheet.
[0024] (3) Preparation of negative electrode The negative electrode graphite material, adhesive PVDF and conductive agent SuperP are evenly mixed in a mass ratio of 90:2:8 to prepare a lithium secondary battery negative electrode slurry with a certain viscosity. The mixed slurry is coated on both sides of the copper foil, dried and rolled to obtain the negative electrode sheet.
[0025] (4) Preparation of lithium-ion batteries The positive electrode sheet, separator, and negative electrode sheet are stacked in order and then stacked as needed. After the tabs are welded, they are placed in the aluminum-plastic film outer packaging of the battery. The prepared non-aqueous electrolyte is injected into the dried bare cell. The cells are then vacuum packaged, allowed to stand, formed (charged at a constant current of 0.05C to 3.9V, then at a constant current of 0.1C to 4.45V), shaped, and tested for capacity, resulting in a 1Ah soft-pack lithium secondary battery.
[0026] The non-aqueous electrolyte formulations of Examples 1 to 17 and Comparative Examples 1 to 3 are shown in Table 1. The steps for preparing the non-aqueous electrolyte and manufacturing the battery are the same as those of Example 1.
[0027] Table 1 Formula of non-aqueous electrolyte
[0028] The lithium-ion batteries prepared in Examples 1 to 17 and Comparative Examples 1 to 3 were subjected to high-temperature storage tests and high-temperature cycle tests, respectively. The specific test conditions are as follows. The performance test results are shown in Table 2.
[0029] Lithium-ion battery high temperature storage performance test At room temperature (25°C), the lithium-ion battery is charged and discharged at 0.3C / 0.3C (the battery discharge capacity is recorded as C0), with an upper limit voltage of 4.45V; the battery is placed in a 60°C oven for 30 days, the battery is taken out, and the battery is placed in a 25°C environment and discharged at 0.3C, with the discharge capacity recorded as C1; then the lithium-ion battery is charged and discharged at 0.3C / 0.3C (the battery discharge capacity is recorded as C2), and the capacity retention rate and capacity recovery rate of the lithium-ion battery are calculated using the following formula: Capacity retention rate = (C1 / C0) × 100% Capacity recovery rate = (C2 / C0) × 100% Lithium-ion battery high temperature cycle performance test Place the lithium-ion battery in a 45°C constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Then charge it at a constant current of 2C to a voltage of 4.45V, then charge it at a constant voltage of 4.45V to a current of 0.05C. Then discharge it at a constant current of 2C to a voltage of 3.0V. Record the first discharge capacity of the battery as C0, which is one charge and discharge cycle. Then, charge and discharge it at 1C / 1C for 1000 cycles at 45°C. Record the discharge capacity as C1. Use the following formula to calculate the capacity retention rate of the lithium-ion battery.
[0030] Capacity retention rate = (C1 / C0) × 100% Internal resistance test Place the separated lithium-ion battery in a 25°C constant temperature chamber and let it rest for 30 minutes to allow the battery to reach a constant temperature. Charge the battery at a constant current of 1C to a voltage of 4.45V, then charge it at a constant voltage of 4.45V to a current of 0.05C. Discharge it at a constant current of 1C to a voltage of 3V. Record the battery's first discharge capacity as C0. This constitutes one charge-discharge cycle. Then, perform 1C / 1C charge and discharge at 25°C for three weeks, discharging it to 0.5C0. Remove the battery and test its DC internal resistance, R.
[0031] High rate cycle performance test At room temperature (25°C), the lithium-ion battery was charged and discharged once at a 3.0C / 3.0C cycle (the battery discharge capacity was recorded as C0) with an upper voltage limit of 4.45V; then, the battery was charged and discharged at a 3.0C / 3.0C cycle for 500 cycles (the battery discharge capacity was recorded as C1), and the capacity retention rate was calculated.
[0032] Capacity retention rate = (C1 / C0) × 100% Table 2 Lithium-ion battery performance test results
[0033] As shown in Table 2, the lithium-ion batteries of Examples 1 to 14 have better high-temperature storage performance, high-temperature cycle performance, and rate cycle performance than those of Comparative Example 1, and have lower internal resistance. This may be because the additives of the non-aqueous electrolyte of the present invention include benzenesulfonyl fluoride compounds and carbonate bisulfate compounds. The synergistic effect between the benzenesulfonyl fluoride compounds and carbonate bisulfate compounds improves the lithium ion transfer rate and rate fast charging performance of the lithium-ion battery, and improves the high-temperature storage performance and high-temperature cycle performance of the lithium-ion battery. It can be seen from Examples 1, 2, 5 and Examples 15 to 17 that the addition of additives to the additives contained in the present invention can further enhance the high-temperature storage and high-temperature cycle performance of the lithium-ion battery of the present invention.
[0034] Further comparison of Example 5 with Comparative Examples 2-3 shows that when only the compound of Structural Formula I or Structural Formula II is used, the high-temperature storage and cycle performance of the lithium-ion battery cannot be taken into account simultaneously, and the improvement effect is lower than that of Example 5. Therefore, the present invention introduces the compounds represented by Structural Formula I and Structural Formula II into the lithium-ion battery electrolyte to increase the ion transfer rate of the lithium-ion battery, form a stable SEI film, reduce the internal resistance of the battery, and improve the high-temperature storage performance and high-temperature cycle performance of the lithium-ion battery.
[0035] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A non-aqueous electrolyte comprising a lithium salt, a non-aqueous organic solvent and an additive, characterized in that: The additives include a benzenesulfonyl fluoride compound shown in structural formula 1 and a carbonate bisulfate compound shown in structural formula 2. wherein R1 to R5 are independently selected from hydrogen atoms, halogen atoms, amino groups, substituted or unsubstituted C1 to C 10 Alkyl, substituted or unsubstituted C2 to C 10 Alkenyl, substituted or unsubstituted C2 to C 10 Alkynyl, R6 to R7 are each independently selected from hydrogen atom, or , * indicates the connection end.
2. The non-aqueous electrolyte according to claim 1, wherein R1-R5 are each independently selected from a hydrogen atom, an amino group, and a substituted or unsubstituted C1-C6 alkyl group, and at least one of R6-R7 is a hydrogen atom.
3. The non-aqueous electrolyte according to claim 1, wherein The benzenesulfonyl fluoride compound is selected from at least one of Compound 1 to Compound 5, 。 4. The non-aqueous electrolyte according to claim 1, wherein The carbonate bisulfate compound is selected from at least one of Compound 6 to Compound 9, 。 5. The non-aqueous electrolyte according to claim 1, wherein The mass percentage of the benzenesulfonyl fluoride compound in the non-aqueous electrolyte is 0.05%-5%, and the mass percentage of the carbonate bisulfate compound in the non-aqueous electrolyte is 0.05%-5%.
6. The non-aqueous electrolyte according to claim 1, wherein The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium bisoxalatoborate, lithium difluorophosphate, lithium fluorosulfonate, lithium difluorooxalatoborate, lithium lower aliphatic carboxylate, lithium difluorobisoxalatophosphate and lithium bisfluorosulfonyl imide.
7. The non-aqueous electrolyte according to claim 1, wherein The non-aqueous organic solvent is selected from at least one of γ-butyrolactone, γ-valerolactone, δ-valerolactone, methyl acetate, ethyl acetate, ethyl propionate, butyl acetate, propyl propionate, butyl propionate, ethylene carbonate, propylene carbonate, butylene carbonate, pentylene carbonate, vinylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl n-propyl carbonate, ethyl n-propyl carbonate, propylene carbonate, 1,3-dioxolane, 1,4-dioxolane, crown ether, tetrahydrofuran, 2-methyltetrahydrofuran, 2-trifluoromethyltetrahydrofuran, dimethoxymethane, diethoxymethane, ethoxymethoxymethane, ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether, and diethylene glycol dimethyl ether.
8. The non-aqueous electrolyte according to claim 1, wherein The invention further comprises an auxiliary agent, which is selected from at least one of fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, vinyl sulfate, 1,3-propylene glycol cyclic sulfate, 1,4-butane sultone, triallyl phosphate and succinic anhydride.
9. A lithium-ion battery, characterized in that The present invention comprises a positive electrode material, a negative electrode material and the non-aqueous electrolyte according to any one of claims 1 to 8, wherein the positive electrode material is selected from nickel cobalt manganese oxide.
10. The lithium-ion battery according to claim 9, wherein The nickel cobalt manganese oxide material is high nickel cobalt manganese oxide LiNi x Co y Mn (1-x-y) M z O2, wherein 0.6≤x<0.9, x+y≤1, 0≤z<0.08, and M is at least one of Al, Mg, Zr and Ti.
Citation Information
Cited By
Electrolyte additive and non-aqueous electrolyte and secondary battery thereof
CN121983670A
Non-aqueous electrolyte, lithium ion battery, battery module, battery pack and electric device
CN122051373A